Clinical pregnancy, live birth, and twin pregnancy outcomes of nine frozen-thawed embryo transfer strategies across female age groups: a real-world cohort study - Lei Sun; Jingjing Huang; Liping Huang; Tian Hu; Weiwei Deng; Hongbo Wu (Frontiers in Endocrinology, 2026)
Background The selection of a frozen-thawed embryo transfer (FET) strategy requires balancing the potential for improved clinical pregnancy and live birth outcomes against the risk of multiple pregnancy. However, comprehensive evaluations of transfer strategies defined by embryo developmental stage (day 3 [D3] cleavage-stage embryos, day 5 [D5] blastocysts, or day 6 [D6] blastocysts), embryo quality (high-quality or non-high-quality usable embryos), and the number of embryos transferred (single or double), particularly in relation to the potential modifying effect of female age, remain limited. In addition, real-world evidence is insufficient to guide clinical decision-making in common scenarios involving patients who have both cleavage-stage embryos and blastocysts available or those who have only D3 cleavage-stage embryos without blastocyst culture. Methods We retrospectively analyzed eligible FET cycles performed at our center between January 2024 and December 2025. Patients were stratified into four age groups: <30, 30–34, 35–39, and ≥40 years. Clinical pregnancy, live birth, and twin pregnancy outcomes were compared across nine embryo transfer strategies. The potential modifying effect of female age on the associations between transfer strategy and clinical pregnancy or live birth was further evaluated. Results Using D5 single high-quality blastocyst transfer as the reference, D5 double high-quality blastocyst transfer was associated with higher odds of clinical pregnancy and live birth, but also with a markedly increased per-transfer-cycle risk of twin pregnancy. D5 double blastocyst transfer comprising one high-quality and one usable blastocyst showed no clear advantage in clinical pregnancy or live birth but was associated with an increased per-transfer-cycle risk of twin pregnancy. D5 single usable blastocyst transfer, D3 single high-quality cleavage-stage embryo transfer, and sequential transfer of two usable embryos were associated with lower odds of clinical pregnancy and/or live birth. D3 double high-quality cleavage-stage embryo transfer was associated with lower odds of clinical pregnancy only, whereas D6 single high-quality blastocyst transfer did not differ significantly from the reference strategy. The adjusted probabilities of clinical pregnancy and live birth generally declined with increasing female age across all transfer strategies. However, no statistically significant age-by-strategy interaction was observed, providing insufficient evidence to support fixed transfer strategies based solely on female age. Conclusions Clinical pregnancy, live birth, and per-transfer-cycle twin pregnancy risk differed across FET strategies. D5 single high-quality blastocyst transfer generally showed favorable reproductive outcomes and a relatively low risk of twin pregnancy and may therefore serve as a clinically relevant reference strategy. D5 double high-quality blastocyst transfer may increase the probability of clinical pregnancy and live birth within a single transfer cycle but is accompanied by a substantially higher risk of twin pregnancy. The current findings do not support selecting a fixed transfer strategy based solely on female age. Clinical decision-making should integrate embryo developmental stage, embryo quality, the number of embryos transferred, baseline patient prognosis, and the risk of multiple pregnancy.